Youth in the midst of escalated political violence: sense of coherence and hope among Jewish and Bedouin Arab adolescents - Sarah Abu-Kaf; Orna Braun-Lewensohn; Tehila Kalagy (BMC, 2017)
Abstract Background During stressful events, individuals (particularly adolescents) from minority groups are often more vulnerable to distress. This claim will be examined in terms of coping resources and stress reactions to escalated political violence. This study aimed to compare coping resources and stress reactions among adolescents from two ethnic groups in southern Israel-Jews and Bedouin Arabs-during a period of escalated political violence (November 2012). The Bedouin Arab group is the ethnic minority of the sample and thus may be more at risk compared to the Jewish group. Methods Data were gathered from 78 Jews and 91 Bedouin Arabs (14-18 years old) by using convenience sampling method. Adolescents were contacted via the Internet or in person by the research team and they completed self-report questionnaires including the Sense Of Coherence Scale (SOC), Hope Index, State Anxiety Inventory, and State Anger Inventory. After a preliminary χ2 analysis of the sample characteristics, three main sets of analyses were conducted including a two-way MANOVA, zero-order correlations between study variables, and hierarchical multiple regressions. Results Bedouin Arab adolescents reported lower levels of SOC (F(1, 158) = 3.88, p = 0.04) and higher levels of individual and collective hope (F(1, 158) = 3.94, p = 0.03; F(1, 158) = 17.41, p = 0.001, respectively), as compared to Jewish adolescents. The Bedouin adolescents also reported higher levels of state anger (F(1, 158) = 5.58, p = 0.02). We identified cultural similarities related to the predictive power of coping resources (SOC and individual hope) in explaining state anger (β = −0.29, p = 0.001; β = −0.18, p = 0.045, respectively). However, cultural differences were found to affect the ability of SOC to predict state anxiety; SOC contributed significantly to state anxiety only among the Jewish adolescents (β = −0.45, p < 0.001). Conclusion These results emphasize the significance of addressing cultural/ethnic factors in attempts to understand mental-health issues among youth during periods of escalated political violence.